Pola Arsitektur Bangunan Istana Niat Lima Laras di Kabupaten Batu Bara - Putri, Indah Rezeki; Achiriah, Achiriah; Azhar, Anang Anas (Mahesa Research Center (PT. Mahesa Global Publishing), 2020)
This article discusses the Architectural Patterns of the Five Laras Niat Palace in Batu Bara Regency. This palace was founded during the reign of Datuk Mad Yudha. This palace has a mix of European, Chinese and Malay style architecture. This study uses the historical method in four writing steps, namely; heuristics, verification or criticism, interpretation, and historiography, with an architectural approach. This palace has unique carvings and decorations. Some of the carvings contained in the architectural pattern of the Five Laras Intentional Palace building, are: Flower Susun Kelapa, Ricih Wajid, Clove Flower, Banana Heart, Dumping Rice, Single Corn, Tapuk Pinang, Bees Bergayut, Endless Tile, Sula Wheel, Crown Flower, A Herd of Ducks Going Home in the Evening, and Arrange Betel. After the death of the Datuk, this palace was slowly being abandoned by the Kedatuan Lima Laras family, because the condition was no longer feasible. Until now, the Niat Lima Laras Palace remains one of the people's pride and is a major historical tourist destination in Batu Bara Regency.